Editorial - Armstrong , Anona (Journal of Law and Governance, 2014)
Ethics and Values in the Corporate World This is the ninth edition of the Journal of Business Systems Governance and Ethics. This edition represents a new chapter in the journal’s history as it is the first to be mounted in the new e-system adopted by VU that will eventually house all the Victoria University journals. The system provides not only journal management but also a greater capacity to access papers and interact with our readers.